2021
DOI: 10.3389/fmolb.2021.628332
|View full text |Cite
|
Sign up to set email alerts
|

The TRAIL in the Treatment of Human Cancer: An Update on Clinical Trials

Abstract: TRAIL (tumor-necrosis factor related apoptosis-inducing ligand, CD253) and its death receptors TRAIL-R1 and TRAIL-R2 selectively trigger the apoptotic cell death in tumor cells. For that reason, TRAIL has been extensively studied as a target of cancer therapy. In spite of the promising preclinical observations, the TRAIL–based therapies in humans have certain limitations. The two main therapeutic approaches are based on either an administration of TRAIL-receptor (TRAIL-R) agonists or a recombinant TRAIL. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 58 publications
0
82
0
Order By: Relevance
“…In phase I and also in phase II clinical trials, mapatumumab has demonstrated a remarkable safety profile and, resulted in complete or partial clinical responses when injected as monotherapy in patients suffering from follicular NHL ( 216 ). Mapatumumab was shown to be well tolerated up to 20 mg/kg daily and its potent therapeutic effects has been investigated for treatment of NSCLC, multiple myeloma, NHL, and HCC ( 216 , 217 ). Currently, a phase II multicenter study on 38 patients suffering from CRC verified the safety but not significant efficacy of the mapatumumab therapy ( 218 ).…”
Section: Trail-r Agonistic Monoclonal Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…In phase I and also in phase II clinical trials, mapatumumab has demonstrated a remarkable safety profile and, resulted in complete or partial clinical responses when injected as monotherapy in patients suffering from follicular NHL ( 216 ). Mapatumumab was shown to be well tolerated up to 20 mg/kg daily and its potent therapeutic effects has been investigated for treatment of NSCLC, multiple myeloma, NHL, and HCC ( 216 , 217 ). Currently, a phase II multicenter study on 38 patients suffering from CRC verified the safety but not significant efficacy of the mapatumumab therapy ( 218 ).…”
Section: Trail-r Agonistic Monoclonal Antibodymentioning
confidence: 99%
“…Among the TRAIL-R2 agonistic antibodies, lexatumumab, drozitumab, DS-8273a, and LBY-135, have completed the phase I clinical trials. Further, tigatuzumab and conatumumab entered the phase II of clinical testing ( 217 ). Investigation of the possible anti-tumor effects of the agonistic antibody (DS-8273a) on 16 patients with advanced cancers evidenced that DS-8273a therapy resulted in the decrease of myeloid-derived suppressor cells (MDSC) in 50% of the patients, supporting DS-8273a utility in combination immunotherapy of cancer ( 221 ).…”
Section: Trail-r Agonistic Monoclonal Antibodymentioning
confidence: 99%
“…Activation of extrinsic apoptotic signaling by TRAIL receptor agonists provoked mutations in surviving cells [ 161 , 162 ], and the minority MOMP and subsequent caspase-mediated mutagenesis provoked by BH3-mimetic drugs facilitated oncogenic transformation in vivo [ 168 ]. TRAIL receptor agonists have not yet been approved for clinical use [ 309 ], and the clinical use of such BH3 mimetics are still in relatively early stages, so the frequency of subsequent cancers in patients treated with these agents will not be evident for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Overcoming TRAIL resistance in melanoma may potentiate the tumoricidal action of the immune system and virtually act in concert with checkpoint inhibitor-targeted immunotherapy. It is noticeable that deregulation of TRAIL-R intracellular signaling, primarily due to aberrant NF-κB activation, often deviates signal from cell death to cell survival ( Snajdauf et al, 2021 ). The well-known FKBP51 role in supporting NF-κB activation ( Romano et al, 2015 ) makes this immunophilin an ideal target to restore TRAIL sensitivity of melanoma.…”
Section: Discussionmentioning
confidence: 99%